Analysis of micromechanical properties of algae bio-based bio-asphalt-mineral interface based on molecular simulation technology. (1st November 2021) - Chen, Wuxing; Chen, Shuang; Zheng, Chuanfeng
Highlights: The bio-asphalt model is established. Molecular dynamics simulation of biological asphalt. Analysis of microscopic properties of bio-asphalt. Abstract: Bio-asphalt is a renewable material with good application prospects. In this study, different ratios of bio-oil were mixed into the base asphalt to simulate bio-asphalt. Through molecular dynamics software, the micro-mechanical properties of the bio-asphalt with different ratios of bio-oil were simulated and studied. By calculating the interfacial energy between asphalt and mineral materials with different amounts of bio-oil, the author found that the higher the amount of bio-oil, the lower the interfacial energy between it and the mineral, which is inversely proportional. Subsequently, the author used molecular dynamics software to analyze the diffusion law of asphalt with different amounts of bio-oil on the surface of mineral aggregates. The simulation results show that the addition of organisms reduces the diffusion rate of asphalt on the surface of the mineral material, thereby affecting the formation of the interface between the asphalt and the mineral material. Therefore, if bio-asphalt is to be widely used in road engineering, it must be modified. The reason for the poor performance of bio-asphalt must be found before modification. The research in this article will provide technical guidance and direction for future modification of bio-asphalt.